Sunshine - Szabó, István (Hungary, 1999)
International co-production: Germany-Canada-Austria-Hungary. Duration: 03:00:00 The film follows three generations of a Jewish family (originally called Sonnenschein, "sunshine" in German, but later changed to Sors, meaning "fate" in Hungarian) during the changes in Hungary from the beginning of the 20th century to the period after the 1956 Hungarian Revolution. Although fictional, the film weaves events drawn from several real sources into the story. The Sunshine family's liquor business was based on the Zwack family's liquor brand Unicum. It was also based at least partly on Hungarian Olympian Attila Petschauer, but also includes allusions to the early life of Miksa Fenyő and other famous Hungarians of Jewish origin who were persecuted in World War II Hungary.